Coliform and Vibrio cholerae Analysis of Drinking Water Collected from Cholera Outbreak Region of Bhaktapur Municipality - Shrestha, Upendra Thapa; Sujakhu, Hishila (International Journal of Environment, 2014)
Water borne infections in Nepal, especially in Kathmandu valley is one the major public health problems, causing thousands of deaths every year. Among three cities in the valley, the water borne infection including cholera is most predominant in Bhaktapur district. So the study was carried out to know the microbial drinking water quality in the city and to determine the prevalence of water borne infections in the specified region of the district in 2012. Altogether eighty (two samples from a single site at different interval-2/3 days) water samples were collected from Bhaktapur Municipality, one of the most vulnerable regions for water borne diseases, following standard methods as described by APHA, 2010. All samples were transferred to Microbiology laboratory of Khwopa College, Dekocha, Bhaktapur and preceded immediately for Microbial analysis. The coliform density in the water samples were determined by Most Probable Number (MPN) method followed by microscopy, colonial morphology and biochemical characterization. Subsequently, the presence of Vibrio cholerae, a causative agent of Cholera was analyzed in the same samples by enrichment in alkaline peptone water followed by culture on Thiosulphate citrate bile-salt sucrose (TCBS) agar, a selective media for Vibrio spp. The biochemical tests were then performed to identify V. cholerae. Among eighty water samples, 87.5 percent water samples contained coliforms and half of which (45%) contained feacal coliforms, Escherichia coli and remaining 12.5 percent water samples contained no coliforms. Vibrio cholerae were isolated from four water samples (5%). The drinking water quality in the region was found to be very poor. Therefore, the people in the region were suggested to treat the drinking water by using any of physical or chemical disinfection methods prior to drinking. DOI: http://dx.doi.org/10.3126/ije.v3i3.11073 International Journal of Environment Vol.3(3) 2014: 139-145